2021
DOI: 10.1007/s12551-021-00839-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanosensitive pathways are regulated by mechanosensitive miRNA clusters in endothelial cells

Abstract: Shear stress is known to affect many processes in (patho-) physiology through a complex, multi-molecular mechanism, termed mechanotransduction. The sheer complexity of the process has raised questions how mechanotransduction is regulated. Here, we comprehensively evaluate the literature about the role of small non-coding miRNA in the regulation of mechanotransduction. Regulation of mRNA by miRNA is rather complex, depending not only on the concentration of mRNA to miRNA, but also on the amount of mRNA competin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…LIS1 OE in the absence of AGO1-4 resulted in a slight but significant increase in a small set of miRs. Data mining revealed that many of these miRs, including members of the let-7 family, miR-221-3p, 16-5p, 296-3p, and others, are involved in mechanotransduction pathways 60, 7785 . RNA seq data further revealed the DE of genes associated with mechanosensitive pathways.…”
Section: Discussionmentioning
confidence: 99%
“…LIS1 OE in the absence of AGO1-4 resulted in a slight but significant increase in a small set of miRs. Data mining revealed that many of these miRs, including members of the let-7 family, miR-221-3p, 16-5p, 296-3p, and others, are involved in mechanotransduction pathways 60, 7785 . RNA seq data further revealed the DE of genes associated with mechanosensitive pathways.…”
Section: Discussionmentioning
confidence: 99%
“…LIS1 OE in the absence of AGO1-4 resulted in a slight but significant increase in a small set of miRs. Data mining revealed that many of these miRs, including members of the let-7 family, miR-221-3p, 16-5p, 296-3p, and others, are involved in mechanotransduction pathways 67 , 88 96 . RNA seq data further revealed the DE of genes associated with mechanosensitive pathways.…”
Section: Discussionmentioning
confidence: 99%